Diseño de un filtro de flujo ascendente para eliminar carga orgánica de las aguas residuales del campus CEASA como tratamiento de la planta anaerobia. - Páramo Maldonado, Charly Eduardo (2024)
Domestic wastewater is the result of the daily use of water in human activities, its direct discharge into water sources can generate notable environmental impacts, in addition to representing a risk to public health. That is why this project is focused on designing an activated carbon upflow filter (FAFA) as a fundamental part of the wastewater treatment responsible for removing the organic load. A precise and detailed methodology was followed for the sizing of the filter, supported by certain design criteria established in the RAS 2000 and the Manual for Anaerobic Upflow Filters of CONAGUA. In addition, the characterization of the flow rate and certain physical-chemical parameters such as DQO and DBO5 were carried out, which are presented as an essential phase in the design process of the upflow filter. The results obtained in the sizing of the FAFA show that the filter has a total height of 3.25 m and a containment volume of 5 m3, suitable for the type of flow that was characterized It should be noted that FAFA has a removal efficiency of 65%. This significant efficiency suggests that the filter is capable of removing almost half of the organic contaminants present in the water, so it can be considered an adequate treatment for the elimination of the organic load. On the other hand, the results of DQO and DBO5 demonstrate that the wastewater from the facilities of the CAREN Faculty has a significant load of biodegradable organic matter. Therefore, it is necessary to generate an adequate treatment to reduce its polluting load. That said, we can highlight the importance of incorporating this type of filter into the water treatment infrastructure of the CEASA Campus. This measure not only leads to a substantial improvement in the efficiency of the treatment system, but also optimizes the process by integrating it with other stages such as secondary sedimentation or filtration. This integration will contribute to a more complete treatment, allowing the most effective reduction of contaminants in the wastewater and a more significant decrease in the organic load.